Страховий ринок України: сучасний стан та проблеми розвитку - Коцюрба, О. Ю.; Насипайко, Д. С.; Kotsiurba, O.; Nasypaiko, D.; Насыпайко, Д. С. (ЦНТУ, 2020)
Статтю присвячено дослідженню особливостей функціонування страхового ринку України в сучасних умовах виникнення нових непередбачених загроз та викликів. Проаналізовано сучасний стан національного страхового ринку та визначено основні тенденції його розвитку у 2017-2020 рр. З’ясовано, що зміна основних показників страхового ринку України відбулась під впливом спаду економіки внаслідок поширення коронорвірусної хвороби. Визначено основні проблеми, які стримують розвиток національного страхового ринку, та вирішення яких забезпечить його становлення як драйвера економічного розвитку країни. The article is devoted to the study of the peculiarities of the Ukraine’ insurance market functioning in the modern conditions of emergence of new unforeseen threats and challenges. The current state of the national insurance market is analyzed and the main trends of its development in 2017-2020 are identified. It was found that the change in the main indicators of the insurance market of Ukraine occurred under the influence of economic downturn due to the spread of coronary heart disease. Thus, if until 2020 the national insurance market was marked by insignificant but stable development, then from 2020 it was significantly affected by restrictive quarantine measures at the state level, which led to a sharp decrease of 19% in gross insurance premiums compared to 2019. There was a decrease in the number of insurers during the study period from 296 to 215, with the largest decrease in the number of companies providing insurance other than life insurance. It is noted that the impetus for the national insurance market development will provide the sale of new insurance products, such as cyber-insurance, P2P insurance and microinsurance, blockchain and smart contracts in insurance, insuretech. The main problems that hinder the development of the national insurance market are identified. These include: the lack of a unified state strategy for the development of the national insurance market, the change of the regulator and, accordingly, the general vision of the development of the national insurance market by its representatives; imperfection and fragmentation of the regulatory framework in the field of insurance; underdeveloped financial market and lack of liquid and reliable financial instruments for investing resources of insurance companies; fears of fraud; low level of innovation by insurers; improper level of information openness of the insurance market, etc. The solution of these problems will ensure its formation as a driver of economic development of the country. Статья посвящена исследованию особенностей функционирования страхового рынка Украины в современных условиях возникновения новых непредвиденных угроз и вызовов. Проанализировано современное состояние национального страхового рынка и определены основные тенденции его развития в 2017-2020 гг. Установлено, что изменение основных показателей страхового рынка Украины состоялась под влиянием спада экономики в результате распространения коронорвирусной болезни. Определены основные проблемы, сдерживающие развитие национального страхового рынка, и решение которых обеспечит его становление как драйвера экономического развития страны.
Insurance Market of Ukraine: Current State and Development Problems
Страховой рынок Украины: современное состояние и проблемы развития
Keywords: страховий ринок; страхові премії; страхові виплати; страхування; страхові компанії; insurance market; insurance premiums; insurance payments; insurance; insurance companies; страховой рынок; страховые премии; страховые выплаты; страхование; страховые компании